A Christian approach to literary criticism : A non- moralistic view - Pretorius, W. G. J. (Koers, 1980)
The common question: “ Is a Christian approach to literary criticism feasible?” may be more profitably reformulated as: “ How should a Christian approach to literary criticism be?”. It is clearly not a matter of the possibility of such an approach, but a challenge of formulating a new critical theory.